Controversy over the Plan for Implementing a Closed Proportional System in the 2024 General Election for the People's Representative Council - Rasji Rasji; Angelia Angelia; Fellicia Angelica Kholim (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Indonesia as a constitutional state has carried out general elections several times in an effort to safeguard people's sovereignty and state democracy. Every citizen has the right to be elected and elect qualified representatives of the people in accordance with statutory provisions. One of the most important aspects in holding general elections is the system used. There are various types of general election systems that have been implemented in Indonesia, one of which is a proportional system which is divided into 2 (two) types, namely an open proportional system and a closed proportional system. Of course, these two systems raise debate in people's lives, there are pros and cons. The development of a proportional system and legislative general elections, especially in the election of members of the People's Legislative Assembly in Indonesia, can be the key answer to choosing this system in general elections in Indonesia. Until finally, this phenomenon made the researchers want to examine the closed proportional system which is said to replace the open proportional system that was implemented in the previous year's General Election. This study uses the research method used in the form of normative research with the approach used is a conceptual approach (conceptual approach) and statutory approach (statute approach) which aims to review the feasibility of the two systems by looking at the advantages and disadvantages.